1977
DOI: 10.1111/j.1365-2133.1977.tb12536.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between lupus erythematosus and lichen planus?

Abstract: Three patients showing features of both lupus erythematosus and lichen planus are described together with their histological, immunofluorescence and other investigative findings. The similarities between lupus erythematosus and lichen planus are discussed and it is suggested that these may be the result of common pathophysiological pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 22 publications
1
12
1
1
Order By: Relevance
“…Lichen planus may occasionally appear clinically similar to lupus erythematosus and histologically both diseases are characterized by an erosive process affecting the lower epidermis. Copeman et al (1970) and Davies et al (1977) have described cases showing features of both lupus erythematosus and lichen planus together and it has been suggested that these may result from common pathophysiological pathways (Davies et al, 1977). Further corroborative evidence that lichen planus may have an immunopathological aetiology is obtained from reports that lichen planus can occur in association with diseases associated with immunological disturbances.…”
Section: Immunopathological Findings In Lichen Planusmentioning
confidence: 96%
“…Lichen planus may occasionally appear clinically similar to lupus erythematosus and histologically both diseases are characterized by an erosive process affecting the lower epidermis. Copeman et al (1970) and Davies et al (1977) have described cases showing features of both lupus erythematosus and lichen planus together and it has been suggested that these may result from common pathophysiological pathways (Davies et al, 1977). Further corroborative evidence that lichen planus may have an immunopathological aetiology is obtained from reports that lichen planus can occur in association with diseases associated with immunological disturbances.…”
Section: Immunopathological Findings In Lichen Planusmentioning
confidence: 96%
“…The signs in LP and in lupus erythematosus may be difficult to distinguish and in each disease be so variable that the overlap might be blamed on a common aetiological agent (Davies et al, 1977), the pathological consequences of which are being expressed in different genetic backgrounds. The genotypic associations are unproven, but seemingly systemic lupus erythematosus is allied to HLA-B7 (Millard, Rowell & Rajah, 1977).…”
Section: P Wmcopeman Et Almentioning
confidence: 99%
“…The clinical presentation of OLP seems to be influenced by the concomitant disease: the erosive form has been reported as more commonly associated with CLD (Bagan et al, 1992 Bologa and Valda, 1971;Grupper et al, 1972Tan, 1974a,b Okoki et al, 1990Cottoni etal., 1991Davies et al, 1977Van der Horst et al, 1983Brenner et al, 1979Connelly et al, 1985Tan, 1972Aronson et al, 1978;Miller, 1971;Samman, 1974Neuman-Jensen et al, 1980Neuman-Jensen et al, 1980Lotem et al, 1989;Lee, 1987Shultleworth et al, 1986Rustin, 1986;Lundstr6m et al, 1982Blasberg et al, 1984Kaplan et al, 1995Zijdenbos et al, 1985Gart, 1994;Bermejo Fenoll andLopez Jornet, 1991 Parodi et al, 1995;Brenner et al, 1979Coltoni et al, 1988Tan, 1974;Mann et al, 1982;Porter et al, 1994;Brenner et al, 1979(Rebora et al, 1978. The results obtained from later research carried out in southern Europeans, particularly in Spain and Italy (Ayala et al, 1986;Cottoni et al, 1988;del Olmo et al, 1989;GISED, 1990), and also in Japanese (Nagao et al, 1995a) (Powell et al, 1983;Mobacken et al, 1984c;…”
Section: (3) Drugsmentioning
confidence: 99%